Effects of caffeic acid phenethyl ester on cerebral cortex: Structural changes resulting from middle cerebral artery ischemia reperfusion - Cengiz, N.; Colakoglu, N.; Kavakli, A.; Sahna, E.; Parlakpinar, H.; Acet, A. (Dustri-Verlag Dr. Karl Feistle, 2007)
Overproduction of free radicals is important in the pathogenesis of the cerebral damage induced by ischemia reperfusion. Caffeic acid phenethyl ester, an active component of propolis extract, exhibits antioxidant properties. The study was carried out in 16 male Wistar albino rats, divided into two groups: ischemia reperfusion and ischemia reperfusion with caffeic acid phenethyl ester. The middle cerebral artery was occluded for 60 min with an intraluminal suture, followed by 24-h reperfusion. In this study, widespread infarcted areas, red neurons (eosinophilic degeneration), pyknotic cells, vacuolization and neuroglial cell infiltration were observed in the cerebral cortex in the ischemia reperfusion group. In the caffeic acid phenethyl ester group, slightly infarcted areas were observed and neuroglial cell infiltration was not determined. Congestion of choroid plexus and pia mater was found more severe in the ischemia reperfusion group than in the caffeic acid phenethyl ester group. In the caffeic acid group, neuroglial cell activation was rare. Vacuolization, an indication of brain edema, was prevented by caffeic acid phenethyl ester. In the present study, we showed that pre-treatment with a single i.p. injection of caffeic acid phenethyl ester at 50 ?M/kg dose reduced the structural changes. ©2007 Dustri-Verlag Dr. K. Feistle.
Keywords: Brain focal ischemia; Caffeic acid phenethyl ester (CAPE); Rat